Interview with Alexandre Anderson - “Today, Guanabara Bay lives apartheid. We are criminalized, they take away the right to come and go” - IDEAS, REVISTA (2015)
The conflicts between large enterprises and local and traditional populations triggered by the appropriation of territories and natural resources of common good by big capital are the order of the day and make up, with a central position, the current framework of discussions held in academia and in social movements about the impacts and consequences of the hegemonic development policy underway in Brazil. The present interview was conducted with Alexandre Anderson de Souza, who is a professional artisanal fisherman, founder and director of AHOMAR, president of the Union of Professional Fishermen and Artisanal Fishermen of the State of Rio de Janeiro (Sindpesca / RJ), member of the Movement's State Executive National Fishermen and Fishermen (MPP) and coordinator of the National Campaign for the Regularization of the Territory of Fishing Communities. Alexandre tells us about AHOMAR's militancy over the disputes that are established between the different forms of uses and appropriations of the fishing territory, its communal spaces and its natural resources. He thus sheds light on a traditional category that has historically been rendered unfeasible and which has been systematically expelled from its territories in the name of the supposed progress provided by the expansion of the frontiers of capital.